Titan the life of John D. Rockefeller, Sr - Chernow, Ron. (London Viking, 2013)
John D. Rockefeller, Sr., history's first billionaire and the patriarch of America's most famous dynasty, is an icon whose true nature has eluded three generations of historians. Now Ron Chernow, a National Book Award winning biographer, gives us a detailed and insightful history of the mogul. Titan is the first full-length biography based on unrestricted access to Rockefeller's exceptionally rich trove of papers. A landmark publication full of startling revelations, the book indelibly alters our image of this most enigmatic capitalist.
Keywords: Roosevelt, Theodore, 1858-1919